(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: Description of the treatment results of patients with adenomyosis undergoing surgery at the National Hospital of Obstetrics and Gynecology (NHOG). Subjects and methods: Descriptive, retrospective study of data from 296 patients with adenomyosis undergoing surgery at the NHOG from January 1, 2022 to December 31, 2023. Results: The rate of patients with simple adenomyosis was 65.5%; adenomyosis and leiomyomas was 34.5%. Patients who underwent laparoscopic surgery accounted for 74.7%; open surgery accounted for 23.0%; laparoscopic surgery converted to open surgery was 2.3%. Bleeding complications encountered during surgery were 2.7% and 1 case of small bowel perforation accounted for 0.4%. The rate of postoperative blood transfusion was 27.0%. The success rate was 97.3%. There were 08 cases of failure (including 07 cases of bleeding and 01 case of small bowel perforation) accounted for 2.7%. The treatment method was related to the number of days in hospital (p<0.05). The success rate of treatment in the group with simple adenomyosis was 98.9%, higher than that in the group with adenomyosis and leiomyomas with 94.1% (p<0.05). Conclusion: Hysterectomy is the only definitive treatment for patients with adenomyosis who have completed childbearing. Treatment outcomes are related to disease subtype classification. However, none of the cases in the study had uterus-sparing surgery.